(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
A pot experiment was conducted under greenhouse conditions in 2023 at Aliko Dangote University Wudil on sandy loam soils of Wudil and Warawa to evaluate the influence of arbuscular mycorrhizal fungi on yield of two cowpea varieties as well as on soil properties and Phosphorus uptake. The treatments consisted of two levels of AMF inoculation (Mo = control, without inoculation, M1 = inoculation with AMF), Two cowpea varieties (Sampea14 and Sampea15) and soils of two location (wudil and warawa). These were laid out in completely randomized design and replicated three times. Data were collected on seeds/pod, 100-seed weight, yield/ha and P uptake. Soil analysis was also carried out before and after the application of treatments. The data were subjected to analysis of variance (ANOVA) using SAS and means were separated at 5% level of significance. Result showed significant effect of AMF on all the yield characters of cowpea (p<0.05). The inoculation of AMF produced higher yield/ha of sampea15 cowpea (874.56kg) than the control (550.42kg). However, there was no significant difference (p>0.05) between yield of the two varieties of cowpea (644.13kg and 780.85kg) used in this study. The application of AMF enhanced the pH (0.22%), organic carbon (0.15%), organic matter content (0.62%) N (0.05%), P (0.16mg/kg) and K (0.18mg/kg) contents of the soil at Wudil and Warawa. Phosphorous uptake of the two cowpea varieties at both locations were also increased more than the control treatments. The study therefore recommends further experiments to study in detail the function of AMF on the...